Exploring Young Adults' Contraceptive Knowledge and Attitudes: Disparities by Race/Ethnicity and Age - Craig, Amaranta D. (2014)
BACKGROUND: Half of pregnancies in the United States are unintended, with the highest proportions occurring among Blacks, Hispanics, and teenagers. Understanding differences in knowledge and attitudes about contraception by race/ethnicity and age can improve efforts to reduce disparities in unintended pregnancy. METHODS: This analysis used data from the 897 female respondents in National Survey of Reproductive and Contraceptive Knowledge, a survey exploring young adults' knowledge and attitudes about contraception and pregnancy. Bivariate and multivariate logistic regression analyses were used to assess racial/ethnic and age group differences in knowledge and attitudes about contraceptives. FINDINGS: Hispanics and teenagers (aged 18–19) had lower awareness of available contraceptive methods, and lower knowledge about individual methods compared with White women and young adults (age 20–29). For example, Hispanics (74%) and teenagers (77%) were less likely to have heard of the intrauterine device (IUD) than were White women (90%) and young adults (90%), and were less likely to know that a woman experiencing side effects could switch brands of oral contraceptive pills (72% of Hispanics vs. 86% of White women; 76% of teenagers vs. 90% of young adults). Hispanics born outside the United States had lower knowledge about contraceptives than U.S.-born Hispanics. For example, foreign-born Hispanics were less likely than U.S.-born Hispanics to have heard of the IUD (59% vs. 82%) or the vaginal ring (55% vs. 95%). CONCLUSIONS: Lower contraceptive knowledge among teenagers and Hispanics, particularly immigrants, suggests the importance of disseminating family planning information to these women as one means to address disparities in unintended pregnancy.